Modes of regulatory governance: A political economy perspective. Issue 1 (27th January 2020) - Guidi, Mattia; Guardiancich, Igor; Levi‐Faur, David
Abstract: This article introduces the special issue by presenting a framework for the study of regulatory politics using the analytical tools and approaches of comparative political economy. Having traced the evolution of studies on regulation, it argues that scholars should pay more attention to the systemic features affecting regulation and to the relationship between regulatory policies and their outcomes. The article presents the foundations of an analytical framework based on the "regulatory policy process, " a comprehensive approach that links inputs, outputs, and outcomes. The review of the contributions to this special issue shows that regulatory regimes can be better understood by placing them within the broader political economy of a state or region. A renewed focus on regulatory outcomes can help foresee what one should expect from the impact of a certain regulatory regime on a political‐economic system.